No need for meat as most customers do not leave canteens on Veggie Days - Christine Merk; Leonie P. Meissner; Amelie Griesoph; Stefan Hoffmann; Ulrich Schmidt; Katrin Rehdanz (npj Climate Action, 2024)
Switching to a diet lower in red meat has the potential to reduce greenhouse gas emissions. Using a unique time series of daily sales data from three German university canteens from 2017 to 2019, we analyse the effects of a monthly Veggie Day in a food-away-from-home context. We find that the temporary ban on meat dishes did not lead to a widespread boycott – as the heated public debates might have suggested. In our setting, a Veggie Day could reduce greenhouse gas emissions by up to 66%. However, especially at the site with a higher share of meat eaters on regular days, up to 22% of customers bypassed the meat-free main dishes on Veggie Days and ate at other on-site alternatives where meat was available. However, total on-site sales did not decrease significantly. Students were less likely to switch to alternatives than staff and guests. A less stringent implementation of a Veggie Day where only beef dishes were removed from the menu, did not result in a significant shift to alternatives but could reduce emissions by up to 51%.
Keywords: 330